Psychic trauma and mental characteristics of patients with multiple sclerosis as predictors of post-traumatic stress disorder and targets for psychotherapy - M. T. Andreeva; T. A. Karavaeva; I. V. Kalinin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article describes the psychological characteristics of the personality of patients with multiple sclerosis (MS), which can be identified as the main targets of psychotherapy for comorbid post-traumatic stress disorder (PTSD). A total of 127 patients with MS were examined, of which 61 patients had symptoms of PTSD that developed in connection with the underlying disease. The control group included 67 MS patients resistant to stress. To assess the structure of personality and psyche, Ammon’s I-structural test was used (G. Ammon, 1976, adaptation by Yu. Ya. Tupitsin, V. V. Bocharov, T. V. Alkhazova, E. V. Brodskaya, 1998). To determine the level of resilience, which is defined as the patient’s ability to navigate in a crisis situation and get out of stress with minimal damage to mental and physical health, D.A. Leontiev (D.A. Leontiev, E.I. Rasskazova, 2006).As a result of the study, it was revealed that patients of the main group have significantly lower scores on all scales of the resilience questionnaire («involvement», «control», «risk acceptance»). At the same time, patients with PTSD are characterized by a higher level of destructive and deficient manifestations of selffunctions on the Ammon scale, in contrast to patients in the control group. Decreased characteristics of hardiness, the predominance of deficient and destructive personality structures are predictors of the onset of post-traumatic stress disorder in patients with MS. The revealed psychological phenomena should be the targets of psychoprophylactic and psychotherapeutic influence in complex programs for the treatment and rehabilitation of these patients.